Therapeutic and treatment procedures in the acute phase of stroke - Tomasz Łapot; Katarzyna Rokosz; Karolina Kumięga (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: The high mortality rate, as well as the percentage of disability resulting from stroke, constitute a significant social and socioeconomic problem. Many countries are introducing prevention programs to minimize the primary and secondary risk factors that trigger stroke. Currently, efforts are being made to raise awareness of the urgent implementation of specialist and effective treatment, and the extremely significant role of physiotherapy introduced immediately at the early stages of stroke is underlined. The objective of work: To present the activities and procedures for a patient with a stroke. Discussion of the principles and goals of early post-stroke rehabilitation, including physiotherapeutic activities undertaken in the case of life-threatening and highly impeding the therapeutic process of stroke complications. The aim of the authors was also to present the current leading methods and concepts of rehabilitation used in early stroke therapy and to review modern methods used in secondary post-stroke rehabilitation. Materials and methods: The article is a narrative review of topics related to therapeutic and management in the acute phase of stroke. The study includes the analysis of literature from the period 2009 to 2021. The database contained books, magazines, and articles. Browsers were used: Google Scholar and PubMed.